Hydropower in New Roles in Changed Context - Bhat, Sher Singh (Hydro Nepal: Journal of Water, Energy and Environment, 2018)
This article focuses on how hydropower can facilitate to integrate more and more renewable in the grid. Doing so, we will have to create new hydropower products and market them. This will be possible if we have a vibrant power market allowing marketing of innovative hydropower products offering primary supply as well as other services in the grid. HYDRO Nepal Journal Journal of Water Energy and Environment Issue No: 22 Page: 48-50 Uploaded date: January 14, 2018